PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI BAGIAN UMUM SETDA KABUPATEN TABANAN - I WAYAN TERIMAJAYA (GANEC SWARA, 2022)
The development of an organization is very dependent on the human resources itself such as work motivation, work environment and job satisfaction which can affect the performance of an organization. The purpose of this study was to analyze the effect of work motivation, work environment and job satisfaction on the performance of employees of the General Secretariat of Tabanan Regency, either partially or simultaneously. This type of research is associative with a sample of 60 employees of the General Secretariat of Tabanan Regency. The results showed that work motivation, work environment and job satisfaction had a significant positive effect partially simultaneously on the performance of the general staff of the Tabanan Regency Secretariat.